2020
DOI: 10.37697/eskiyeni.673386
|View full text |Cite
|
Sign up to set email alerts
|

Türkiye’de Yapılan ‘Dinî Başa Çıkma’ Konulu Araştırmalar Hakkında Bir Değerlendirme

Abstract: This research deals with the studies of "Religious coping", which were carried out in Turkey between 2001-2019. Coping can be defined as a cognitive and behavioral effort to diminish the chaos and the psychological pressure caused by stressful situations. People often confront unpleasant event and situations disturbing them psychologically and physiologically. Every person wants to overcome this kind of nuisances in order to protect his/her psychological and physiological health. In order to manage these unpl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 28 publications
0
3
0
5
Order By: Relevance
“…In all of the studies conducted on religious coping, it was found that religion contributed to overcoming problems and protecting mental health. Common results found in studies is that especially positive religious coping contributes positively to mental health (Abanoz, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…In all of the studies conducted on religious coping, it was found that religion contributed to overcoming problems and protecting mental health. Common results found in studies is that especially positive religious coping contributes positively to mental health (Abanoz, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…These rich diversity sources in Turkish society may be considered an obstacle to benefiting from the sources of religion during the counseling process. The place of religion in psychological counseling processes will be a topic of discussion (Abanoz, 2020;Dilmaç et al, 2016). However, considering the human characteristics of the psychological counselors, it can be suggested that how religion affects counseling process in the Turkish community be studied, as well.…”
Section: Discussionmentioning
confidence: 99%
“…İkinci yöntem, Lazarus ve Folkman'ın 1984'te ortaya koyduğu "sorun/problem odaklı" ve "duygu odaklı" baş etme yöntemleridir. Sorun odaklı baş etme yöntemleri ile birey sorunu çözmeye odaklanırken duygu odaklı baş etme yönteminde hissettiği olumsuz duygulardan kurtulmaya odaklanır (Abanoz, 2020).…”
Section: İşsizliğin Olumsuz Etkileri Ve Bu Olumsuzluklarla Başetme Y...unclassified